A FDI Attack-Resilient Distributed Secondary Control Strategy for Islanded Microgrids - Chen, Yulin; Qi, Donglian; Dong, Hangning; Li, Chaoyong; Li, Zhenming; Zhang, Jianliang (IEEE transactions on smart grid, 2021)
Distributed cooperative control has been used as a preferred secondary control strategy for maintaining frequency synchronization and voltage restoration in cyber-physical AC microgrids due to its flexibility, scalability and better computational performance. However, such a control system is susceptible to potential cyber attacks, i.e., false data injection (FDI) attacks. To this end, this article introduces a hidden layer based attack-resilient distributed cooperative control algorithm to solve the problem of the secondary control of islanded microgrids under FDI attacks. In comparison to the existing attack-resilient distributed control methods, the proposed controller with sufficient large α can mitigate the adverse effects of time dependent FDI attacks on actuators, sensors and communication links of the control system, and is also robust to state dependent FDI attacks. Furthermore, the algorithm is applicable even when all DGs and communications are compromised. Finally, the efficiency of the proposed controller is evaluated for a test microgrid with 4 DGs under different types of attack.